Genome-wide analysis of the G-box regulating factors protein family reveals its roles in response to Sclerotinia sclerotiorum infection in rapeseed (Brassica napus L.) - Sun, Qinfu; Xi, Ying; Lu, Panpan; Lu, Yingying; Wang, Yue; Wang, Youping (Frontiers in Plant Science, 2022)
The G-box regulating factors (GRFs) are involved in a wide array of signal transduction pathways and play important roles in plant physiological and developmental processes and stress responses. The GRF proteins have previously been described in several plant species, but not in rapeseed (Brassica napus L.). In this study, we carried out a genome-wide analysis of GRFs in B. napus based on the available genome sequence information, and analyzed their expression in different tissues under different hormone treatments and after inoculation with Sclerotinia sclerotiorum. We identified 46 putative BnaGRF genes in rapeseed, unevenly distributed on 18 chromosomes. Like the 14-3-3 proteins in other plant species, the 46 putative BnaGRFs could be classified into two major evolutionary branches: epsilon (ɛ) group and non-epsilon (non-ɛ) group. Evolutionary analysis indicated that the BnaGRF gene family expanded in both groups much before speciation. We discovered an expansion of the BnaGRF gene family that likely occurred during a recent gene duplication event. Collinearity analysis revealed that most of the BnaGRF genes shared syntenic relationships. Global gene expression profiling of BnaGRFs by RNA-seq analysis showed a 41.3% (19/46) response to S. sclerotiorum infection, and this response was probably mediated through jasmonic acid (JA) and salicylic acid (SA) signaling pathways. These results provide key insights into the role of BnaGRFs in the biotic stress response and enhance our understanding of their multiple functions in B. napus.